Correlation between mandibular trabeculae bone density on panoramic radiograph and body mass index of men aged 5-35 years old - Binar Barlian; Azhari Azhari; Farina Pramanik (Journal of Dentomaxillofacial Science, 2018)
Objective: Finding the correlation between mandibular trabeculae bone density on panoramic radiograph and body mass index of men aged 5-35 years old.Material and Methods: The population of this study was male patients aged 5-35 years old who performed panoramic radiography at Radiology Installation of Faculty of Dentistry at RSGM UNPAD with a total of 62 samples. ImageJ software was used to calculate the bone density and BMI values were calculated using the BMI formula.Â Results: The score of body mass index increased with age meanwhile the score of mandibular trabeculae bone density decreased.Conclusion: The r-value of this study was -0.341. There was no correlation between mandibular trabeculae bone density on panoramic radiographs and body mass index of men aged 5-35 years old.